Partial replacement of soybean meal with mixed plant proteins yields comparable growth and carcass quality in growing-finishing pigs - Zhao, Wei Han; Ha, Joo Hyun; Cho, Sungbo; Kim, In Ho (Frontiers in Veterinary Science, 2025)
ObjectiveThis study evaluated the impacts of partial replacement of soybean meal with different concentrations of mixed plant protein products (rapeseed meal (RSM) - palm kernel meal (PKM) -distillers dried grains with soluble (DDGS)) on growth performance and carcass quality of growing-finishing pigs.MethodsA total of 180 crossbred [Yorkshire x Landrace] pigs with average initial weight of 29.72 + 1.65 Kg were randomly assigned to one of five dietary treatment groups on the basis of weight and sex, and the experimental duration was 105 days. The basal diet (C23ON) of growing and finishing pigs were partially replaced with increasing level of RSM-PKM-DDGS (1 to 5% for growing pigs, and 2 to 6% for finishers). Each treatment group had 9 replicate pens, each containing 2 barrows and 2 gilts. During the 15-week trial, body weight (BW), average daily gain (ADG), average daily feed intake (ADFI), and feed conversion ratio (FCR) were calculated for the periods of weeks 0–5, weeks 5–10, week 10–15, and for the entire experimental period.ResultsThe partial replacement of soybean meal with mixed plant protein products (RSM, PKM-DDGS) showed no significant effect on the growth performance of pigs during the entire experimental period (p > 0.05). However, a decreasing ADG (p = 0.0837) and ADFI (p = 0.0779) were observed during weeks 0–5, while an increasing FCR was noted during weeks 10–15 (p = 0.0835) and the overall period. Furthermore, the replacement of soybean meal with mixed plant protein products (RSM-PKM-DDGS) showed no linear or quadratic effects on the digestibility of dry matter (DM), nitrogen (N), energy (E), fecal scores, or meat quality.ConclusionThis suggests that mixed plant protein products (RSM, PKM, and DDGS) can effectively replace soybean meal as the primary protein source, providing comparable outcomes while potentially reducing feed costs.